Upaya Penguatan Perekonomian Masyarakat Pasca Tambang Karst - Fadlilah, Khaerul (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Karst mines in the Mount Kromong area cannot be separated from the historical aspects of local communities in utilizing karst resources as a support for their necessities of life. Historically the use of karst in the area of Mount Kromong has been going on since 1700 and has been passed down from generation to generation. However, the change in control of the karst mining area resulted in various significant changes to people's lives so that various alternative economic sectors emerged that needed to be strengthened through empowerment efforts. This study aims to examine how the post-mining Cikeusal Village community's economy has changed and how the Village Government's efforts to strengthen community alternative economic sectors after the mining sector has become exclusive. So, the questions that will be formulated by researchers in this study are (1) What is the history of karst mining management in Cikeusal Village?; and (2) How is the post-karst mining economic empowerment process in Cikeusal Village? Researchers used qualitative research methods with a case study approach. Data collection techniques used by researchers are observation, interviews and documentation while data analysis techniques used by researchers are simple time series analysis. In this research, the researcher outlines the data obtained in the field during the time the research took place chronologically as well as a description of the dynamics of the post-mining community economic empowerment process in Cikeusal Village.